Role of Axillary Lymph Nodes Involvement in Some Complications of Modified Radical Mastectomy - Hussein Abbas Obaid; Mohammed Radhi Mohammed; Haider Hussein Abd (Medical Journal of Babylon)
Background: Modified radical mastectomy (MRM) is an excellent surgical approach for breast cancer. Some complications following mastectomy are wound infection, lymphedema, and seroma. Objectives: To explore lymph node involvement role in some complications of MRM. Materials and Methods: A prospective study enrolling 100 women with breast cancer admitted to Baghdad Teaching Hospital from January 2015 to January 2018. Data about demography, past medical history, family history, and other relevant data were taken. We did MRM with axillary lymph nodes excision level one, two, and three, depending on the lymph node involvement extent. According to the number of lymph nodes involved, patients were allocated into group one (1–3 lymph nodes), or two (4–9), or three (10 or more). Follow-up lasted 2 years after surgery to detect wound infection, lymphedema, and seroma. Results: Wound infection, lymphedema, and seroma occurred more in patients of group three; however, only lymphedema and seroma showed a significantly different rate among the three groups. Conclusions: The number and degree of lymph nodes involvement is an important factor in the occurrence of lymphedema and seroma.